Analysis of early relaparotomy following living donor liver transplantation. Issue 11 (November 2016) - Hara, Takanobu; Soyama, Akihiko; Hidaka, Masaaki; Kitasato, Amane; Ono, Shinichiro; Natsuda, Koji; Kugiyama, Tota; Imamura, Hajime; Okada, Satomi; Baimakhanov, Zhassulan; Kuroki, Tamotsu; Eguchi, Susumu
Abstract : We retrospectively analyzed the causes, risk factors, and impact of early relaparotomy after adult‐to‐adult living donor liver transplantation (LDLT) on the posttransplant outcome. Adult recipients who underwent initial LDLT at our institution between August 1997 and August 2015 (n = 196) were included. Any patients who required early retransplantation were excluded. Early relaparotomy was defined as surgical treatment within 30 days after LDLT. Relaparotomy was performed 66 times in 52 recipients (a maximum of 4 times in 1 patient). The reasons for relaparotomy comprised postoperative bleeding (39.4%), vascular complications (27.3%), suspicion of abdominal sepsis or bile leakage (25.8%), and others (7.6%). A multivariate analysis revealed that previous upper abdominal surgery and prolonged operative time were independent risk factors for early relaparotomy. The overall survival rate in the relaparotomy group was worse than that in the nonrelaparotomy group (6 months, 67.3% versus 90.1%, P < 0.001; 1 year, 67.3% versus 88.6%, P < 0.001; and 5 years, 62.6% versus 70.6%, P = 0.06). The outcome of patients who underwent 2 or more relaparotomies was worse compared with patients who underwent only 1 relaparotomy. In a subgroup analysis according to the cause of initial relaparotomy, the survival rate of the postoperative bleeding group was comparable with the nonrelaparotomy group ( P = 0.96). On the other hand, the survival rate of the vascular complication group was significantly worse than that of the nonrelaparotomy group ( P = 0.001). Previous upper abdominal surgery is a risk factor for early relaparotomy after LDLT. A favorable longterm outcome is expected in patients who undergo early relaparotomy due to postoperative bleeding. Liver Transplantation 22 1519–1525 2016 AASLD .